Proteinaceous methanotrophs for feed additive using biowaste as carbon and nutrients source. (October 2020) - Tsapekos, Panagiotis; Zhu, Xinyu; Pallis, Evangelos; Angelidaki, Irini
Graphical abstract: Highlights: Biomethane and extracted nitrogen from biowaste were used to grow methanotrophs. Supplementation of 100 μgCu 2+ /L increased the biomass production by more than 40%. More than 2.5 g/L was produced by a Methylomonas enriched community. The total amino acids counted more than 50% of dry cell weight. Abstract: To achieve a sustainable production of food and feed production, inexpensive carbon and nutrient sources are needed. In the present study, biologically upgraded biogas is coupled with electrochemically extracted nitrogen from digested biowaste to cultivate mixed methanotrophs as protein source. Results showed that an increase from less than 5 μgCu 2+ /L to 100 μgCu 2+ /L increased the biomass production by 41%. Microbial analysis revealed that the dominated Methylomonas spp. followed by Methylophilus spp. created a specialized community for high CH4 assimilation. Moreover, duplicate semi-continuous fermenters run for 120 days validating the efficiency of alternative carbon and nitrogen feedstocks at long-term operation. As for dry cell weight (DCW) production, more than 2.5 g-DCW/L were produced using biologically upgraded biogas and electrochemically extracted nitrogen. Furthermore, the protein content and amino acid profile (>50% of DCW) demonstrated that the microbial biomass pose the characteristics to be used as animal feed additive.